Biofertilizers, Nitrogen and Phosphorus on Yield and Nutrient Economy in Forage Sorghum Affected by Nutrient Management in Preceding Mustard - Ramanjaneyulu, A. V.; Giri, G.; Kumar, S. R. (International Journal of Bio-resource and Stress Management, 2010)
The results of field experiment conducted during 2003-04 and 2004-05 revealed that green and dry fodder yield of sorghum were highest when the crop received recommended dose of fertilizer (RDF) at 60 kg N+30 kg P2O5 ha-1, but the crop yielded comparable green and dry fodder when it received half RDF (30 kg N+15 kg P2O5 ha-1) +biofertilizers (Azotobacter+phosphate solubilizing bacteria). Further, RDF and half RDF+biofertilizers enhanced the dry fodder yield by 45.8 and 41.2%, respectively over control. The highest agronomic efficiency (57 kg dry fodder kg-1 N applied), net return (INR 5190 ha-1) and benefit-cost ratio (1.45) were also obtained with half RDF+biofertilizers. On the contrary, the crop removed significantly greater amount of N and P when supplied with RDF, while RDF and half RDF+biofertilizers were at par and significantly superior to half RDF and control in respect of K uptake. RDF (80 kg N+40 kg P2O5 ha-1) applied to preceding mustard significantly out yielded all other treatments in respect of green fodder yield of sorghum barring residual half RDF+biofertilizers. Residual RDF and half RDF+biofertilizers enhanced dry fodder yield by 31.6 and 27.0%, respectively